Six Notes on Latin Correlatives - Probert, P; Dickey, E (2015)
This chapter raises several interrelated questions and makes some observations concerning the Latin 'relative-correlative' construction: quos ferro trucidari oportebat, eos nondum uoce uolnero (Cicero, Cat. 1. 9) '(Those) who ought to have been put to death by the sword, them I am not (even) wounding with my voice yet.' Our central concern is the chronological distribution of the construction. It has often been noted that relative-correlative sentences are most plentiful in early Latin texts and appear to decline in frequency thereafter: they are less common but still clearly present in classical texts and then distinctly rare after the classical period, in both high-register and low-register texts. This is a curious chronological distribution. Did the construction decline sharply after the classical period because it counted as substandard or because it became too difficult to produce? Neither explanation makes obvious sense: it is difficult to see how a construction used by Cicero in his speeches could have come to count as substandard, yet it is also difficult to see how a high-register construction could have fallen out of use even among highly classicising late writers. The explanation for the overall decline of the construction has most often been seen in the widespread but by no means universal idea that Proto-Indo-European relative clauses were exclusively of the relative-correlative type. We do not take this explanation to be self-evidently sufficient, and one of us has argued elsewhere against the idea that all relative clauses in Proto-Indo-European were of the correlative type. We therefore think it worth asking once again quite why the relative-correlative construction declined in Latin. In order to do so, we raise a question about the synchronic structure of the construction (Note 1) and provide some evidence that this construction does indeed have the chronological distribution just outlined (Note 2). Notes 3 – 6 more directly address the reasons for the observed decline in frequency.